Colour–magnitude diagrams of transiting exoplanets – III. A public code, nine strange planets, and the role of phosphine. Issue 1 (17th August 2020) - Dransfield, Georgina; Triaud, Amaury H M J
ABSTRACT: Colour–magnitude diagrams provide a convenient way of comparing populations of similar objects. When well populated with precise measurements, they allow quick inferences to be made about the bulk properties of an astronomic object simply from its proximity on a diagram to other objects. We present here a python toolkit that allows a user to produce colour–magnitude diagrams of transiting exoplanets, comparing planets to populations of ultra-cool dwarfs, of directly imaged exoplanets, to theoretical models of planetary atmospheres, and to other transiting exoplanets. Using a selection of near- and mid-infrared colour–magnitude diagrams, we show how outliers can be identified for further investigation, and how emerging subpopulations can be identified. Additionally, we present evidence that observed differences in the Spitzer 's 4.5 μ m flux, between irradiated Jupiters and field brown dwarfs, might be attributed to phosphine, which is susceptible to photolysis. The presence of phosphine in low-irradiation environments may negate the need for thermal inversions to explain eclipse measurements. We speculate that the anomalously low 4.5 μ m flux of the nightside of HD 189733b and the daysides of GJ 436b and GJ 3470b might be caused by phosphine absorption. Finally, we use our toolkit to include Hubble Wide Field Camera 3 spectra, creating a new photometric band called the 'Water band' ( WJH band) in the process. We show that the colour index [ WJH − H ] can be used to constrain the C/O ratio of exoplanets, showing that future observations with James Webb Space Telescope and Ariel will be able to distinguish these populations if they exist, and select members for future follow-up.